Condition Assessment of OLTC Using Duval Triangle and Static Winding Resistance Test - Ahmad Khiar, Mohd Shahril; Md Thayoob, Yasmin Hanum; Yang Ghazali, Young Zaidey; Ab Ghani, Sharin; Sutan Chairul, Imran (2012)
On Load Tap Changer (OLTC) failure occurs is due to the insulation degradation and contacts failure inside it. Other than that, contacts wear influences the OLTC performances. The worn contacts will cause hotspots in the OLTC tank and cause the insulating oil to degrade faster. As a result, this will lead to the damage of complete transformer unit. Thus, the research work that has been carried out applied the Dissolved Gas Analysis (DGA) via latest Duval Triangle method during the diagnosis of OLTC at the first stage to provide early indication of OLTC’s breakdown. The Static Winding Resistance Test is then applied at the second stage to figure out any increase of contact resistances for all phases. The capability of Static Winding Resistance Test in order to provide any sign of bad contacts in fixed condition can be done by comparing two different conditions which are before and after maintenance.